Trabalho e sofrimento do policial militar do estado de Goiás - Lima, Denise Michelle Valério de (2018)
The present work had its objective to analyze the organization of the Military Police work of the State of Goias and its relation with the experience of suffering at work. In pursuit of this objective, I sought to investigate the characteristics of this organization and to identify the experiences of pleasure-sufferingin in this activity, as well as the defensive strategies used by the military police officers in the development of their positions. The theoretical contributions that supported the research was the psychodynamics of the job, which has as object of the study the dynamic relations between the organization of work and the processes of subjectivities. These can be manifested in experiences of pleasure-suffering, strategies of mediation of the contradictions existing in work, in pathologies or even in health experiences and that strengthen the identity. The instrument used for data collection was the individual semi-structured interview and data analysis was performed using the Thematic Categorical Content Analysis technique. It was observed in the data obtained and analyzed that, the pleasure is referred in the activities in which the autonomy and the technical capacity of each police officer can be used, as well the perception of being useful by the job that they render to the society. The experiences of suffering are mentioned before the existing obstacles due to the hierarchy; due to the lack of recognition and career advancement and to the misunderstanding observed in the custody hearings. Thus, they manifest as feeling of pleasure; satisfaction; passion; motivation; happiness. And as feelings that describe suffering ; guilt; omission; frustration; sadness; dissatisfaction; fear. As impacts of the work, it was observed its reflex in the physical, psychological and family life, being the Extra Compensated Service pointed as a factor that contributes considerably in this sense.